Towards direct detection of gold bearing rock formations from seismic data: St. Ives gold camp, Western Australia - Harrison, Christopher; Urosevic, Milovan (Society of Exploration Geophysics, 2008)
The utilization of seismic methods for mineral exploration, particularly in Western Australia has become widespread in the last few years. In the initial stage the use of seismic data was limited to the structural interpretation only. Subsequent lithological interpretation however required introduction and testing of new techniques and methodologies, such as inversion and attributes analysis. While these techniques are considered mature by hydrocarbon standards, their application in hard-rock environments still requires extensive study to determine the veracity of the results. Challenges to hard-rock seismic methods begin at the acquisition phase where factors such as remoteness and inaccessibility of the site and environmental restrictions, result in seismic lines being misaligned with the dip of the dominant structures. Further, massive shear zones, faulting, folding, and dyke intrusions, common for these areas, result in extremely complex subsurface structures which also compound seismic images. The regolith, a near surface zone up to 150 meters thick comprised of altered, transported, and weathered material causes energy dissipation and time delays in seismic mapping of hard rock environments. The lack of borehole data with sonic logs also contributes to the difficulty of seismic data calibration and hence full utilization and analysis of seismic information. Preservation of amplitude, frequency content and phase of original signal is a prerequisite for inversion and attribute analysis. However, the complex structure, seen in mineral exploration in Western Australia, makes this task cumbersome. Inherently low signal to noise ratio and variable receiver and source ground coupling, presents a problem for true amplitude processing of hard rock seismic data. We show that each of the challenges facing hard-rock seismic has a systematic solution. This leads towards the final aim which is to accomplish the lithological interpretation by directly relating seismic impedance and attributes to the various rock formations in contact.